THE ROLE OF WORK MOTIVATION IN MODERATING INDIVIDUAL FACTORS THAT INFLUENCE EMPLOYEE PERFORMANCE - Diana Sulianti K Tobing; Markus Apriono; Sudarsih Sudarsih; Nyoman Gede Krishnabudi; Salsabila Salsabila (EKUITAS (Jurnal Ekonomi dan Keuangan), 2024)
The purpose of this study is to ascertain how work motivation, acting as a moderating variable, influences employee performance in the Jember Regency Forestry State-Owned Enterprise by mediating individual factors such as organizational commitment, career development, and individual characteristics. The research sample consisted of 157 respondents. The research utilizes both primary and secondary data. The study methodology employed is the Interaction Test, often known as MRA (Moderated Regression Analysis). The study's findings demonstrate that individual traits (X3), career advancement (X2), and organizational commitment (X1) all significantly and partially improve employee performance (Y). Work motivation (Z) has the potential to either attenuate or enhance the impact of organizational commitment (X1) on employee performance (Y). Work motivation (Z) has the potential to either decrease or enhance the impact of career growth (X2) on employee performance (Y). Work motivation (Z) has the potential to either attenuate or enhance the impact of individual attributes (X3) on employee performance (Y). The research suggests that the firm's capacity to sustain a harmonious work motivation can foster loyalty to the company, as well as a drive to deliver high performance for the company.